2021
DOI: 10.3390/diagnostics11112072
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multimodal Management of Post-Partum Synchronous Metastatic Pulmonary EBV-Associated Lymphoepithelioma-Like Carcinoma (LELC)—A Case Report

Abstract: Primary Epstein-Barr-Virus (EBV)-associated pulmonary lymphoepithelioma-like carcinoma (LELC) is an aggressive rare cancer. Higher incidences have been observed in Asian sub-populations. Multimodal treatment paradigms have emerged as promising novel strategies in the management of advanced NSCLC. In this report, we describe the case of a 34-year-old female patient of Asian origin with a post-partum initial diagnosis of pulmonary LELC. Multimodal treatment with chemoimmunotherapy and hypofractionated irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In Asia, the incidence of PLELC is approximately 0.9% of NSCLC cases ( 1 , 2 ). Studies have reported on PLELC in Guangdong Province ( 3 ), Hong Kong ( 1 ), and Taiwan ( 4 ), but only a few cases have been described in reports from Western countries ( 5 ). PLELC tends to occur in younger, nonsmoking females ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the incidence of PLELC is approximately 0.9% of NSCLC cases ( 1 , 2 ). Studies have reported on PLELC in Guangdong Province ( 3 ), Hong Kong ( 1 ), and Taiwan ( 4 ), but only a few cases have been described in reports from Western countries ( 5 ). PLELC tends to occur in younger, nonsmoking females ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our previous case report described the therapy strategy of multi-site hypofractionated radiotherapy and chemoimmunotherapy for a metastatic pulmonary EBV-associated lymphoepithelioma-like carcinoma [15].…”
mentioning
confidence: 99%